Certificação ISO 9000 e aprendizagem organizacional: o caso SEBRAE - Leite, Evandro Sérgio Martins (2003)
The perception of theorganizational members ofthe Serviço de Apoio às Micro e Pequenas Empresas do Estado deMato Grosso do Sul - SEBRAE/MS situated in Campo Grande, MS, about the ISO Certification implanted in that institution since 1998 and the organizational learning was aimed to study. It was sought to provide a link of the certification as a factor stimulator of organizational learning. Withrelationship to the methodology, it is treated of a case study being used group the methods ofqualitative and quantitative research. The data were collected with the applications of semi-structured questionnaires and personal interview, direct observations and documental analysis. The profiles of the 94 direct collaborators and questioned 58 collaborators which have been in the organization since before the implantation of the certification. The quantitative data were tabulated and analyzed, by utilizing Software SPSS (Statistical Packagefor the SocialScience). Theperception of the interviewed was positive as regards the certification as in terms of linkage to organizational learning in the following aspects: understandings relative to the concepts and importance of the certification; commitment of the organizational members, process of democratization of the decisions and actions; continuous learning; leadership; and interpersonal relationship and with the foreign clients. It follows that the ISO 9000 Certification together to the SEBRAE/MS served to impulse the organizational learning and e implantation of uniforms standards in the productive systemof the organization. And in a approachoftotal qualitypersists the focus on the client, partnership with the suppliers and emphasis on the preparation of the inside collaborators. At present, the enterprise does not concentrate upon exclusively on the maintenance ofthe standards established in the ISO Certification process. Organizational Learning is characterized by continuous improvements and was shown in the research the rooting before the organizational member, in this approach,searching not only the maintenance of the certification itselfbut also new challenges.